Effectiveness of Organizational Communication channels used by Hwange Colliery Company to communicate with its Publics to enhance corporate reputation. (2010-2012) - Masuku, Caven; Zulu, Perseverance (International Journal of Innovative and Applied Research, 2014)
The purpose of this study is to assess the Effectiveness of Organizational Communication channels used by Hwange Colliery Company to communicate with its Publics to enhance corporate reputation. This is because effective communication has been the pillar to the success of many big corporate organizations and this prompted the researcher to study a local organization, Hwange Colliery Company. In this study literature was reviewed from scholars that had prior knowledge on the topic of organizational communication and its importance in the day to day running of organizations. The theoretical framework in the study focuses on the process of communication; this was done to enable the researcher to have a better understanding of the importance of organizational communication in at Hwange Colliery Company. The study would be informed by four theories namely Lasswell model of communication, Shannon and Weaver’s communication transmission model, Schramm’s model of Communication and bureaucracy theory. Furthermore, the study implies triangulation that is the use of both qualitative and quantitative research methods to attain information closer to reality and validity. The research methods used include interviews, questionnaires and participant observation as data gathering techniques as they were the most suitable in collecting data from the different publics at HCCL. Recommendations were made to enable the organization to achieve maximum efficiency in communication. Improvements that are required are mentioned so as to help future research.